2017
DOI: 10.1089/chi.2015.0151
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Physical Activity and Sedentary Behavior in Youth with Type 2 Diabetes

Abstract: Subjective PA measures validated in the general youth population may not be the best method for differentiating levels of movement in overweight/obese youth with type 2 diabetes, who spend most of their time in light-intensity activity and sedentary pursuits with little or no time spent in moderate/vigorous-intensity activities. Objective measures such as accelerometers that can capture the lower end of the movement scale are likely the more appropriate measures under these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…For example, the built environment [ 34 ], peer relationships [ 35 ], and the day of the week [ 36 ] have all been shown to influence the levels of sedentary behavior in children. Other retrospective self-report tools for assessing sedentary behavior, such as the outdoor playtime recall questionnaire, are unable to provide such details surrounding sedentary behaviors and have demonstrated weak correlations with the accelerometer-measured ST [ 37 , 38 ]. Therefore, EMA may be more effective at capturing factors relevant to ST than other self-report measures previously utilized by investigators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the built environment [ 34 ], peer relationships [ 35 ], and the day of the week [ 36 ] have all been shown to influence the levels of sedentary behavior in children. Other retrospective self-report tools for assessing sedentary behavior, such as the outdoor playtime recall questionnaire, are unable to provide such details surrounding sedentary behaviors and have demonstrated weak correlations with the accelerometer-measured ST [ 37 , 38 ]. Therefore, EMA may be more effective at capturing factors relevant to ST than other self-report measures previously utilized by investigators.…”
Section: Discussionmentioning
confidence: 99%
“…When sports or exercise was reported in the past 2 h via EMA, significantly more minutes of MVPA were recorded by accelerometers during this time frame, and this was consistent with previous findings in adults [ 41 ]. A recent study comparing retrospective self-reports of PA and accelerometer-measured PA in youth found no relationship between the two [ 37 ]. Moreover, participants have been shown to overestimate the amounts of PA that they engaged in by an average of 596 minutes per week when utilizing retrospective questionnaires [ 17 ], highlighting the need for more effective self-report methods, particularly in children.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the built environment [27], peer relationships [28], and day of week [29] have all been shown to influence levels of sedentary behavior in children. Other retrospective self-report tools for assessing sedentary behavior, such as the Outdoor Playtime Recall Questionnaire, are unable to provide such details surrounding sedentary behaviors and have demonstrated weak correlations with accelerometer-measured ST [30,31]. Therefore, EMA may be more effective at capturing factors relevant to ST than other self-report measures previously utilized by investigators.…”
Section: Discussionmentioning
confidence: 99%
“…When sports/exercise were reported in the past two hours via EMA, significantly more minutes of MVPA were recorded by accelerometers during this time frame. A recent study comparing paper self-reports of PA and accelerometer-measured PA in youth found no relationship between the two [30]. Moreover, participants have been shown to overestimate the amounts of PA that they engaged in when utilizing questionnaires [14], highlighting the need for a more effective self-report methods, particularly in children.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers utilize various subjective and objective techniques as well as PA dimensions (FITT) to characterize and interpret PA. There are numerous studies using thresholds to derive PA intensity (or PA level , i.e., categorized PA intensity) to quantify human PA (Clemente et al, 2016; Vanroy et al, 2016; Krüger et al, 2017; Laakkonen et al, 2017; McCarthy et al, 2017; Rockette-Wagner et al, 2017; Vanderloo and Tucker, 2017). However, it is controversial whether defined thresholds for assessing PA levels can be applied to people from different age groups.…”
Section: Introductionmentioning
confidence: 99%